HISTORIA Y NARRATIVA. LA HACIENDA GANADERA GUANACASTECA. ANÁLISIS DE LAS NOVELAS “LA ESTIRPE DEL VOLCÁN” Y “EL FESTÍN DE LOS COYOTES” - Rivera Hernández, Gina (2008)
In recent years it has aroused great interest in reassess the history of the Costa Rican regions, and within this collective effort, the province of Guanacaste, it shows as a fertile ground for the analysis of different angles. In this perspective, we have raised the analysis of two novels set in the social, political, gender and productive that occur in development of the basic unit of fundiaria in the area, as is the hacienda. We seek to compare with it, the concordant and discordant visions of narrative given by "The Feast of the Coyotes' Victor Quirós (1990) and" The lineage of the Volcano "Rocio Pazos (2002), as sources for understanding particular interpretations of the reality and literary inspiration that generates the hacienda in various social sectors in the province of Guanacaste, in contrast to the historical facts given by texts such as Lowell Gudmunson, Wilder Sequeira and Marc Edelman, among others.